IMPLEMENTASI IoT DAN SENSOR CERDAS PADA MOBIL LISTRIK UNTUK MENINGKATKAN EFISIENSI ENERGI - Meilisa Apriyani; Nelson Marcelino; Dorie P. Kesuma (CV. Denasya Smart Publisher, 2026)
The rapid development of electric vehicles has encouraged the integration of Internet of Things (IoT) technology and intelligent sensor systems to improve energy efficiency, driving safety, and real-time monitoring capabilities. This study aims to analyze the implementation of IoT and smart sensors in electric vehicles as part of smart transportation systems. The research method used is a qualitative approach through literature review by collecting data from scientific journals, conference proceedings, and recent publications related to electric vehicles, IoT systems, and automotive sensors. The results show that IoT integration in electric vehicles enables real-time monitoring of battery conditions, energy consumption, vehicle location, temperature stability, and driver behavior. In addition, the use of sensors such as ultrasonic sensors, temperature sensors, GPS modules, LiDAR, and battery management sensors significantly improves operational efficiency and driving safety. However, challenges remain in terms of cybersecurity, infrastructure readiness, implementation costs, and data integration complexity. This research is expected to contribute to the development of smart electric transportation systems that are more efficient, safe, and sustainable in the future.